KAJIAN PENGAMANAN PERIMETER DALAM MENUNJANG KEAMANAN PENERBANGAN DI BANDAR UDARA INTERNASIONAL ADI SOEMARMOSURAKARTA - Amanda Nurma Hariyanti; Satiti Utami; Herman Susanto (Politeknik Penerbangan Indonesia Curug, 2019)
The objektive of research to know and inspect connecting withthe safety and safety of flights at Adi Soemarmo International Airport is still found a variety of distractions that are there land boundaries or territories that are under the supervision of the airport. This limit is one that limits the area of aircraft movement, as well as air navigation equipment facilities and other important installations of all obstacles (obstacle) that can harm flight safety. With the current perimeter security, the perimeter fence at Adi Soemarmo International Airport has not functioned properly, namely to prevent psycology and physic, preventing intrusion and help detection/ Arrest, provide controlled doors/access for people and vehicles.It is directly or indirectly affects the safety of flights at Adi Soemarmo International Airport. To be able to realize optimal security at the perimeter of the Adi Soemarmo Intenational Airport, it is necessary to base the rules of flight that has been set, thereby supporting safe, smooth, convenient and efficient operation of aviation at Adi Soemarmo International Airport